The stranger in the lifeboat [compact disc, unabridged] : a novel - Albom, Mitch, 1958- (Harper Audio, 2021)
Adrift in a raft after a deadly ship explosion, nine people struggle for survival at sea. Three days pass. Short on water, food and hope, they spot a man floating in the waves. They pull him in. Thank the Lord we found you, a passenger says. I am the Lord, the man whispers. Is this strange and quiet man really who he claims to be? What actually happened to cause the explosion? Are the survivors already in heaven, or are they in hell? The story is narrated by Benji, one of the passengers, who recounts the events in a notebook that is later discovered, a year later, when the empty life raft washes up on the island of Montserrat. It falls to the island's chief inspector, Jarty LeFleur, a man battling his own demons, to solve the mystery of what really happened.